STRATEGY FOR INCREASING THE COMPETITIVENESS OF MADRASAH - Sodik, Jakfar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the models and strategies for increasing competitiveness at Madrasah TsanawiyahMiftahulMidadLumajang. Over the years, this madrasa has been in terrible condition. However, it has risen drastically in the last few decades and proved a superior and competitive madrasah. This change is then interesting to study so that other madrasas can later duplicate the achievements of this madrasa. This research is qualitative research with a case study approach. Observation, interviews, group discussions and document searches were conducted for data collection. This research found that the leading factors of the madrasa head, learning innovation, teachers, and quality madrasa facilities are the main aspects that can improve the quality and competitiveness of this madrasa. These factors have made this madrasa achieve achievements in various fields and made people flock to send their children to this madrasah.